2017
DOI: 10.18203/2394-6040.ijcmph20173856
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic determinants of paediatric tuberculosis patients in an urban city of Central India

Abstract: Background: Paediatric tuberculosis (TB) indicates presence in the community of sputum -positive pulmonary tuberculosis, presence of childhood risk factors for disease and stage of epidemic. This "orphan disease" exists in the shadow of adult TB and is a significant child health problem, but is neglected. As a result both research and surveillance data in the field of childhood TB has been greatly limited. Objective of the study was to find out the socio-demographic profile of paediatric TB patients registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…7 Similarly, Joshi S et al, showed that fathers of 24.24% paediatric patients were illiterate, 13.93% were from middle school, 13.33% from primary school, 32.12% high school. 12 10.30% were intermediate, 4.24% were graduate and the fathers with highest level of education i.e. post-graduation was 1.81% only.…”
Section: Discussionmentioning
confidence: 97%
“…7 Similarly, Joshi S et al, showed that fathers of 24.24% paediatric patients were illiterate, 13.93% were from middle school, 13.33% from primary school, 32.12% high school. 12 10.30% were intermediate, 4.24% were graduate and the fathers with highest level of education i.e. post-graduation was 1.81% only.…”
Section: Discussionmentioning
confidence: 97%
“…Evidence on existence of sex-based differences among pediatric TB cases is mixed with few previous studies from India reporting higher proportion of TB cases among female children [23][24][25][26][27]. Speculated reasons for this finding include neglect of the girl child in the family in terms of vaccination and nutrition resulting in poor immunity, parents lacking motivation to seek care for the girl child leading to delayed access to appropriate care, and lack of health awareness among girls due to lack of proper education [23,[25][26][27]. Nevertheless, it is to be noted that most studies report absolute numbers and proportions of MTB diagnosed cases received from lab reports.…”
Section: Discussionmentioning
confidence: 99%